2017
DOI: 10.12657/denbio.079.007
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the effect of regional climate fluctuations on Quercus robur L. trees under a temperate continental climate (southern Romania)

Abstract: Interpreting the effect of regional climate fluctuations on Quercus robur L. trees under a temperate continental climate (southern Romania) Received: 6 July 2017; Accepted: 27 November 2017 Abstract: To determine oak tree sensitivity to climate fluctuations as a precipitation predictor, we eliminated monthly climate data and computed the growth-precipitation correlation using mean daily values calculated in time intervals. Precipitation from March through May is the primary limiting factor in intra-annual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Additionally, ash EW development can be affected by severe winter-spring droughts or intense frost events [71]. Our findings regarding the oak RW/LW positive response to previous autumn and current spring to summer precipitation agree with other studies from Western [72], Southern [3,14,26,69], and Eastern Europe [24,25,68,84,85], where the water availability is considered the main driving factor for oak growth. Even if these oak trees are growing in a steppe environment, EW does not retain a significant response to precipitation, having a similar reaction with oaks in different environmental conditions from Europe [68,69].…”
Section: Correlation With Temperature and Precipitationsupporting
confidence: 89%
“…Additionally, ash EW development can be affected by severe winter-spring droughts or intense frost events [71]. Our findings regarding the oak RW/LW positive response to previous autumn and current spring to summer precipitation agree with other studies from Western [72], Southern [3,14,26,69], and Eastern Europe [24,25,68,84,85], where the water availability is considered the main driving factor for oak growth. Even if these oak trees are growing in a steppe environment, EW does not retain a significant response to precipitation, having a similar reaction with oaks in different environmental conditions from Europe [68,69].…”
Section: Correlation With Temperature and Precipitationsupporting
confidence: 89%
“…Growth responses to climatic parameters can vary depending on the climatic zone (boreal, temperate, or continental), growing season, type of ecosystem (steppe, tundra, or rainforest), tree species, etc. (Dulamsuren et al, 2011;Köse et al, 2012;Liang et al, 2012;Bhuyan et al, 2017;Nechita & Chiriloaei, 2018). Previous studies in drought regions have shown that precipitation is the most important limiting factor for tree-ring growth (Touchan & Hughes, 1999;Köse et al, 2012;Fonti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, it has been intensively studied across Europe and also Romania thanks to its great economic, ecological and social importance [69][70][71], being one of the most valued tree species in temperate forests [72]. It is a light-demanding species and it can tolerate a broad spectrum of site conditions, being resistant to dry winds and droughts [73,74]. In particular, its seedlings can grow in a wide range of shade levels, from heavy shade to direct light [75].…”
Section: Resultsmentioning
confidence: 99%